Information Technology Factors Contributing To Effective Change Implementation In Telekom Sales And Services Sdn. Bhd. : A Company Formed Through A Merger - Che Ahmad, Che Abdul Rahim (2000)
The high expectations set for any merger are usually what contribute to the management's decision to proceed with such a move. The success of transformation change has been the subject of many studies, and the aspect of information technology (IT) as a factor for effective change can be an interesting subject to cover.